FEATURES OF THE SYSTEMATIZATION-INTEGRATION OF CONFLICT MANAGEMENT METHODS IN HIGHER EDUCATIONAL INSTITUTIONS - Petrosyan, M. (SUSh Scientific Proceedings, 2025)
Educational reforms that have been ongoing for many years have led to serious changes in the structure of the administrative and management apparatus of many universities: an increase in the flow of documents, changes in the rules for organizing the educational process, and changes in the rights and obligations of the parties. Each university sets innovative strategic goals to increase the quality of education. The current pace of development of society determines the introduction of changes in various aspects of the activities of universities, and these changes may meet with resistance from employees and students, which will lead to the emergence of conflict situations, which ultimately lead to complications. The education system has been reformed for many years, and ongoing reforms place new demands on educational organizations, pushing for a variety of organizational changes. The constant changes and transformations taking place in universities create tension and increase conflict in the relationships between participants in the educational process. Our practical experiment shows that it is difficult to avoid conflict situations in higher education, so it is more rational to direct research efforts to finding effective technologies, conflict management mechanisms, and modern methods in higher education [7, 24].